Heidenhain Variant of Creutzfeldt-Jakob Disease in Brazil: A Case Report - Laura Furtado Pessoa de Mendonça; Pedro Maia Nobre Rocha Saffi; Luciana Lilian Louzada Martini; Luciano Farage; Einstein Francisco Camargos (Brazilian Society of Geriatrics and Gerontology, 2024)
Creutzfeldt-Jakob disease (CJD) is a rare spongiform encephalopathy characterized by a rapid neurodegenerative progress, caused by a misfolded variant of the cellular prion protein (PrP) known as PrPSc. The clinical presentation of sCJD includes a wide range of neurological signs of cortical, subcortical, or cerebellar origin, either isolated or in various combinations. Due to this protean clinical presentation form, sCJD must be distinguished from other dementias. In this case report, we discuss the Heidenhain variant of Creutzfeldt-Jakob disease (HvCJD), a rare variant characterized by early visual symptoms and typical findings in imaging scans. Our patient presented rapidly progressive dementia and a history of visual hallucinations. As for other prion diseases, only symptomatic treatment is available for HvCJD. Thirty years of clinical investigation of patients with prion disease have resulted in little progress in either defining or evaluating potential treatments.